2012
DOI: 10.1016/j.enbuild.2012.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the solar irradiation potential for solar photovoltaic applications in buildings at low latitudes – Making the case for Brazil

Abstract: a b s t r a c tIn Brazil, a low-latitude country characterized by its high availability and uniformity of solar radiation, the use of PV solar energy integrated in buildings is still incipient. However, at the moment there are several initiatives which give some hints that lead to think that there will be a change shortly. In countries where this technology is already a daily reality, such as Germany, Japan or Spain, the recommendations and basic criteria to avoid losses due to orientation and tilt are widespr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 21 publications
1
20
0
7
Order By: Relevance
“…When a threshold is used, its value differs between countries and sources, e.g. the acceptable ratio of available to maximum irradiation for an optimally inclined and oriented surface ranges from 55% to 80% [9]. Assessment methods also differ in the number of metrics, as in the case of solar energy potential assessments based on solar maps, which offer from one output (i.e.…”
Section: Performance Criteria Evaluation Metricmentioning
confidence: 99%
See 1 more Smart Citation
“…When a threshold is used, its value differs between countries and sources, e.g. the acceptable ratio of available to maximum irradiation for an optimally inclined and oriented surface ranges from 55% to 80% [9]. Assessment methods also differ in the number of metrics, as in the case of solar energy potential assessments based on solar maps, which offer from one output (i.e.…”
Section: Performance Criteria Evaluation Metricmentioning
confidence: 99%
“…Many publications deal with a unique and specific criterion, for instance related to the daylight performance [51,35], or the photovoltaic (PV) and/or solar thermal (ST) potential [22,18,9,16]. Other studies also evaluate a unique metric, but one which is meant to represent the performance in a broader sense: Otis [33] and van Esch et al [49] measure winter and summer solar exposure in terms of radiation, with this measure being linked to the passive performance of buildings and the thermal comfort of outdoor spaces.…”
Section: Performance Criteria Evaluation Metricmentioning
confidence: 99%
“…The geometry of roof shape has an influence on the surface area that determines the number of PV modules that can be installed such as a hip roof. A comprehensive study conducted in the Southern hemisphere by Cronemberger [11] that observed the availability of solar potential yield in 78 Brazilian cities located between latitude 0° and 30° S (0° ≤ ø ≤ 30° S) to evaluate the suitability of the buildings' envelopes for photovoltaic. They identified optimal tilt angle of fixed surfaces in 78 Brazilian cities using secondary data that published by the World Radiation Data Center.…”
Section: The 3 Rd International Seminar On Science and Technology 85mentioning
confidence: 99%
“…In this work, the value of q g is assumed to be 0.2 [16,41,50,51] for all months and locations due to the Malaysian weather of having less climatic changes and no snow cover throughout a year. The value is ordinarily satisfactory and accepted in most of the engineering practices as reported by other research works.…”
Section: Modelling Of Solar Irradiation On Inclined Surfacesmentioning
confidence: 99%
“…They proposed to alter the optimum tilt angle twelve times annually in which the output was quantitatively comparable to the daily changing optimum tilt angle. Cronemberger et al [41] evaluated the received solar radiation intensity on various surfaces of Brazilian building for photovoltaic application at latitudes between 0°and 30°S. They indicated the optimum value could be up to 9°above the latitude.…”
Section: Introductionmentioning
confidence: 99%